2015
DOI: 10.1039/c5cp03195h
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effect of a non-permeating component on gas permeability of nanoporous graphene membranes

Abstract: We identify the inhibition effect of a non-permeating gas component on gases permeating through the nanoporous graphene membranes and reveal its mechanisms from molecular dynamics insights. The membrane separation process involves the gas mixtures of CH4/H2 and CH4/N2 with different partial pressures of the non-permeating gas component (CH4). The results show that the permeance of the H2 and N2 molecules decreases sharply in the presence of the CH4 molecules. The permeance of the N2 molecules can be reduced to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Huang et al [85] demonstrated that the permeance (2.4 9 10 5 GPU for H 2 ) and selectivity (10 24 at room temperature) were significantly improved for the separation of H 2 /CH 4 by adopting an inter-layer-connected porous graphene bilayer. In a recent work by Wen et al [86], an inhibition effect of non-permeating components on the permeation of permeating component was identified ( Fig. 2e).…”
Section: Theoretical Workmentioning
confidence: 70%
“…Huang et al [85] demonstrated that the permeance (2.4 9 10 5 GPU for H 2 ) and selectivity (10 24 at room temperature) were significantly improved for the separation of H 2 /CH 4 by adopting an inter-layer-connected porous graphene bilayer. In a recent work by Wen et al [86], an inhibition effect of non-permeating components on the permeation of permeating component was identified ( Fig. 2e).…”
Section: Theoretical Workmentioning
confidence: 70%
“…For example, tiny but precise holes can be used for desalinating sea water [197] and potentially for separating different gases [198,199]. The desired porosity can be achieved in a number of ways, such as ion bombardment [200,201], electron beam irradiation [202], chemical etching and surface-assisted aryl-aryl coupling of cyclohexa-m-phenylene [203,204]. A free-standing nanoporous monolayer graphene membrane is a single atom thick (∼3 Å) , which is close to the stacking distance (∼3.4 Å) of a DNA base pair [205].…”
Section: Ultrafiltration Mediummentioning
confidence: 99%
“…Therefore, the molecular adsorption on both sides of the graphene surface is in a quasiequilibrium state. It is noted that, in the simulations, the separations of CO 2 and H 2 S molecules from CH 4 molecules are conducted separately; in the event that the CO 2 and H 2 S molecules are mixed together and simultaneously separated from CH 4 molecules, the adsorption of one component would be decreased due to the competitive mechanism, which can induce a reduction in the permeation rate of this component, as illustrated by Wen et al [34].…”
Section: Molecular Adsorptionmentioning
confidence: 99%
“…Until now, most of the relevant studies have been conducted based on theoretical calculations due to their practicability and low economic cost, especially in regard to molecular dynamics (MD) and density functional theory methods. The effects of surface adsorption [31][32][33], nonpermeating component [34], chemical modifications [35,36] and others on molecular permeation were elucidated. Lei et al [37] tested the sieving effect of a pristine graphene nanopore for the separation of H 2 S/CH 4 and revealed the effects of atomic charges by adding charges on the pore-rim carbon atoms.…”
Section: Introductionmentioning
confidence: 99%